Effect of the Two Types of Exploitation on Organizational Ambidexterity and Firm Performance: Analysis in the Japanese Video Game Industry - Taiki ITO (AAOS Transactions)
Recent organizational ambidexterity studies have discussed the importance of achieving a balance between exploration and exploitation. However, existing studies have not distinguished the detail of exploitation, this study breaks down exploitation into repetitive exploitation and incremental exploitation. Our study contributes to ambidexterity studies by analyzed the impact of the combination of this two exploitation and exploration in firm performance. Using Japanese video game industries' 674 observations from 1997 to 2019 as panel data analysis, like the existing studies, we proved that firm performance is increased when exploration and exploitation balance is achieved. At the same time, we found that firms with a lower exploration had higher performance when the rate of incremental exploitation was high. The results of our study suggest that even when the firm's ambidexterity is imbalance, different results can be expected when the details of exploitation are considered.